Impact of low investment return on bonus rates of with-profits products. - Lee, Wai Yi. (2010)
Life insurance products these days have become more than a means of protection against unforseen events. Products which allow the policyholder to participate in the profits of the insurance companies have become excellent savings instruments which can offer attractive rewards in the form of bonuses. In fact, they are being marketed aggressively by the salesforce, alongside other non-insurance savings vehicles. These with-profits products constitute the core of almost all life insurance companies' businesses, and bonus distribution becomes an important issue to grapple with. In order to compete with other life insurance companies as well as non-insurance financial instruments, local companies have been declaring attractively generous bonus rates. This is fine as long as the investment performance of the life fund is on the uphill. However, in the past decade or so, figures seem to indicate that the net investment return on the life fund has been on the decline. With the recent economic crisis, it seems even more certain that the low investment return environment will stay longer than expected.